Adverse childhood experiences and diurnal cortisol patterns in older people in England. (August 2022) - Demakakos, Panayotes; Steptoe, Andrew
Abstract: Adverse childhood experiences (ACE) are associated with HPA axis dysregulation at younger ages, but there is scarcity of evidence for this association at older ages. To add to our knowledge of the lifetime impact of ACE on HPA axis function, we examined whether ACE were associated with diurnal cortisol patterns in a national sample of 587 participants (356 women) aged 55–79 years from the English Longitudinal Study of Ageing (ELSA). We conducted descriptive analyses and estimated sex-specific robust regression models of the associations between the 8-item summary ACE score and four measurements of salivary cortisol over a 24-h cycle (upon waking, 30 min later, at 7 pm, and at bedtime) as well as the cortisol awakening response (CAR) and the diurnal cortisol slope. Our models were adjusted for age, then for childhood socioeconomic position and finally for adult socioeconomic position. In men, we found significant differences that were independent of covariates, with more ACE being associated with lower salivary cortisol levels on waking, a greater CAR, and a flatter diurnal cortisol slope. In women, we observed a graded association between ACE and increased 7 pm salivary cortisol levels. Our findings indicate that childhood adversity is related to HPA axis in older people, especially men. The chronological distance (on average >50 years) between ACE and salivary cortisol levels suggests the existence of a lifelong association between childhood adversity and HPA axis and neuroendocrine function. Notwithstanding sex differences, based on our findings we suggest that HPA axis dysregulation could be a pathway that mediates the association between ACE and chronic disease later in life. Highlights: ACE were associated with salivary cortisol levels and patterns in people aged 55-79 years. These associations were graded. In men, ACE were associated with lower salivary cortisol levels on waking, greater CAR and flatter diurnal cortisol slope. In women, ACE were associated with increased 7pm salivary cortisol levels. Socioeconomic position did not explain the associations and thus they cannot be fully attributed to socioeconomic disadvantage. The chronological distance (on average >50 years) between ACE and the salivary cortisol points to a lifelong association. HPA axis dysregulation qualifies to be a mediating pathway of the association between ACE and chronic disease at older ages.